A Review of the Ethno-dentistry Activities of Calotropis gigantea - Ningsih, Diana Setya; Celik, Ismail; Abas, Abdul Hawil; Bachtiar, Boy Muhclis; Kemala, Pati; Idroes, Ghazi Mauer; Maulydia, Nur Balqis (Malacca Pharmaceutics, 2023)
Calotropis gigantea is a medicinal herb that thrives in arid climates. All parts of this plant are rich in secondary metabolites, which are very beneficial for health. Phytochemicals of this plant include flavonoid, alkaloids, steroids, cardiac glycosides, and terpenoids, which have a wide range of pharmacological effects. The potential of metabolit compound from C. gigantea can be used in dental treatment. This review describes the potential use of C. gigantea in ethno-dentistry, specifically as anti-caries, soft tissue inflammation (periodontitis and gingivitis), degenerative diseases (tumor/cancer), and wound healing. This review provides general perspectives and basic literature on the use of C. gigantea in the field of etno-dentistry.